A Tourism Village Planning Strategy Using the SOAR Model in Penglatan Village, Buleleng Regency, Bali - Wirasetia, Putu Andi; Widiastini, Ni Made Ary; Rahmawati, Putu Indah (Journal of Business on Hospitality and Tourism, 2022)
Penglatan Village is one of the villages in Buleleng district which is famous for its typical food, namely dodol and the art of sound art, namely Renganis. Penglatan Village has tourism potential that has not been optimally packaged and marketed. Therefore, this study aims to explore the feasibility of Penglatan village to be developed and to analyze the tourism potential it has as a tourism village to build sustainable tourism in Buleleng Regency. This study uses a qualitative research approach. Data collection methods used were interviews, observation, documentation and FGD (Focus Group Discussion). The tourism potential includes, among others, middle culture of furniture, the "samyag dresti" temple, tourism of the Yellow Temple, multi-purpose halls, carving works, Kencana Mas hill temple, dodol and belayag culinary tours, Jelema wood trees, songket crafts, and pathways tracking/cycling. The existence of some of these tourism potentials has received a good response from tourists such as dodol and belayag culinary tours, but there is still a lot of potential that has not been explored and packaged properly, such as the Kuning Temple water tour. The development planning strategy using SOAR analysis in Penglatan village which is applied to 11 tourism potentials by analyzing the points of strength, opportunity, aspiration and result for each tourism potential to support the village Penglatan as a tourist village.